2021
DOI: 10.1038/s42004-021-00569-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical shielding of H2O and HF encapsulated inside a C60 cage

Abstract: Molecular surgery provides the opportunity to study relatively large molecules encapsulated within a fullerene cage. Here we determine the location of an H2O molecule isolated within an adsorbed buckminsterfullerene cage, and compare this to the intrafullerene position of HF. Using normal incidence X-ray standing wave (NIXSW) analysis, coupled with density functional theory and molecular dynamics simulations, we show that both H2O and HF are located at an off-centre position within the fullerene cage, caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Such data from experimental observations are available only for the ground 101a,a',b ortho‐H 2 O state, while the theoretical studies predict the lifting of degeneracy for higher excited rotationally states, too. Just recently, an energy splitting of 2.9 cm −1 has been also reported [16] for the translational transition N=0N=1 of ortho‐H 2 O from IR absorption spectroscopy experiments, while X‐ray experiments coupled with DFT and molecular dynamics simulations have just shown that H 2 O is located at an off‐center position inside the C 60 [34] . Definitely, the observation of such phenomena requires deeper investigation from both theory and experiment.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Such data from experimental observations are available only for the ground 101a,a',b ortho‐H 2 O state, while the theoretical studies predict the lifting of degeneracy for higher excited rotationally states, too. Just recently, an energy splitting of 2.9 cm −1 has been also reported [16] for the translational transition N=0N=1 of ortho‐H 2 O from IR absorption spectroscopy experiments, while X‐ray experiments coupled with DFT and molecular dynamics simulations have just shown that H 2 O is located at an off‐center position inside the C 60 [34] . Definitely, the observation of such phenomena requires deeper investigation from both theory and experiment.…”
Section: Discussionmentioning
confidence: 92%
“…As emphasized earlier, [27] in lack of full dimensional firstprinciples/ab initio interaction energies, we may speculate for various possible interaction terms in the potential and/or nuclear motion couplings, that could be able to match experimental evidences. In this vein, by introducing anisotropy in the n-mode potential expansion, [27] according to recent electronic structure calculations [33] and X-ray experimental evidences, [34] due to noncolavent interactions in interfullerene environment, [33,[35][36][37][38][39][40] we have also computed rotational states splitting patterns in qualitative accord to those observed experimentally. [3,10] Theoretical investigations of such unconventional features require fully coupled quantum treatments.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations